Syndicated lending : structuring and implementing syndicated credits - Fight, Andrew; Shepherd, Gavin le F (London : Euromoney Institutional Investor, 2000)
Syndicated Lending aims to increase the readers awareness of the benefits and risks involved in taking part in the Syndicated Loan market. This book covers: *Who the major players in the syndication loan market are *Why syndication loans are used *Syndication loan structures and documentation *Secondary syndication loan market *Inspired from the basic entry level training courses that have been developed by major international banks worldwide.
Self Study Solutions
Title taken from slip cover and inside front page of each vol
oif 30/06/14, ijb 11/03/2019
Loan
Keywords: Syndicated loans; Syndicates (Finance).